1998
DOI: 10.1097/00001756-199807130-00039
|View full text |Cite
|
Sign up to set email alerts
|

GDNF administration induces recovery of the nigrostriatal dopaminergic system both in young and aged parkinsonian mice

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a member of the transforming growth factor beta superfamily and acts as a neurotrophic factor for the nigrostriatal dopaminergic system. GDNF was injected stereotaxically into the striatum of young (2 months old) and aged (12 months old) C57BL/6 mice that were treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) 1 week earlier. Immunocytochemical and neurochemical analyses showed significant recovery of the nigrostriatal dopaminergic system both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…GDNF has pronounced neurorestorative effects on dopaminergic markers in mice (Tomac et al, 1995a;Date et al, 1998) or monkeys (Gash et al, 1996;Zhang et al, 1997) when administered after MPTP and shows neuroprotective effects on the concentrations of dopamine and its metabolites when administered before or during MPTP administration (Kojima et al, 1997;Cheng et al, 1998). There is one report of protective effects against MPTPinduced death of dopaminergic SNpc neurons (Tomac et al, 1995a), showing enhanced survival of ipsilateral and contralateral dopaminergic neurons when GDNF was stereotaxically injected above the substantia nigra of one side.…”
Section: Discussionmentioning
confidence: 99%
“…GDNF has pronounced neurorestorative effects on dopaminergic markers in mice (Tomac et al, 1995a;Date et al, 1998) or monkeys (Gash et al, 1996;Zhang et al, 1997) when administered after MPTP and shows neuroprotective effects on the concentrations of dopamine and its metabolites when administered before or during MPTP administration (Kojima et al, 1997;Cheng et al, 1998). There is one report of protective effects against MPTPinduced death of dopaminergic SNpc neurons (Tomac et al, 1995a), showing enhanced survival of ipsilateral and contralateral dopaminergic neurons when GDNF was stereotaxically injected above the substantia nigra of one side.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous glial cell line-derived neurotrophic factor (GDNF) treatment has been reported to reverse some of the age-related, DA-mediated motor and phenotypic declines in rodents (Bowencamp et al, 1996;Emerich et al, 1996;Hebert and Gerhardt, 1997;Lapchak et al, 1997;Date et al, 1998). The ability of GDNF to restore both DA phenotype and motor behavior in aged animals suggests that sufficient nigral DA neurons remain to respond to the trophic factor, which would be extremely unlikely if these cells were lost during aging.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, delineating molecular mechanisms that regulate survival of the SNC dopaminergic neurons may provide an avenue for better treatment or prevention of PD. To this end, numerous studies in vitro, in animal models that recapitulate PD, and in human PD patients, have shown that glial cell-line derived neurotrophic factor (GDNF) family ligands (GFLs) promote increased survival of SNC dopaminergic neurons, reduce functional deficits caused by dopaminergic toxins, and improve parkinsonian symptoms (Gash et al, 1996;Cheng et al, 1998;Date et al, 1998;Horger et al, 1998;Kordower et al, 2000;Tomac et al, 2000;Sun et al, 2004;Jakobsen et al, 2005). GFL ligands (GDNF and Neurturin) have been, or are in clinical trials in the treatment of PD (Gill et al, 2003;Slevin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%